ANALISIS KUALITAS PRODUK DAN DISKON TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA TOKO THRIFT DINDA SAYUDHA DI SITUBONDO - Aziza, Aziza; Ediyanto, Ediyanto; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2023)
The aim of the research is to find out the analysis of product quality and discounts on consumer satisfaction through purchasing decisions as an intervening variable at the Thrift Dinda Sayudha store in Situbondo. The sampling technique in this study was simple random sampling. Data analysis and hypothesis testing in this study used Partial Least Square (PLS-SEM) The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that product quality has a positive and significant effect on purchasing decisions, discounts have a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on consumer satisfaction, discounts have a negative and insignificant effect on satisfaction consumers, purchasing decisions have a positive and significant effect on consumer satisfaction, product quality has a positive and significant effect on consumer satisfaction through purchasing decisions, discounts have a positive and significant effect on consumer satisfaction through purchasing decisions.